Ofatumumab for multirelapsing membranous nephropathy complicated by rituximab-induced serum-sickness. Issue 1 (23rd January 2020) - Podestà, Manuel Alfredo; Ruggiero, Barbara; Remuzzi, Giuseppe; Ruggenenti, Piero
Abstract : Rituximab (375 mg/m 2 ) achieved remission of the first episode and six relapses of nephrotic syndrome (NS) in a young male patient with podocyte phospholipase A2 receptor (PLA2 R)-related membranous nephropathy (MN) refractory to steroids and cyclosporine. Between-treatments interval averaged 17.4±4.2 months. The seventh infusion was complicated by delayed serum-sickness, which resolved with steroids. On subsequent relapse, the fully human anti-CD20 monoclonal antibody ofatumumab (300 mg) achieved remission of the NS, without significant side effects. Circulating CD19 + B cells were depleted, proteinuria decreased from 10.9 to 1.3 g/day, and serum albumin, immunoglobulin levels and glomerular filtration rate normalised. Twenty-eight months later, despite transient anti-PLA2 R depletion, ofatumumab (100 mg) failed to induce remission of the eighth relapse. Remission was safely achieved 5 months later with repeated ofatumumab infusion (300 mg). This treatment (€723) was less expensive than rituximab (€1801). Ofatumumab could be a safe and cost/effective rescue therapy for patients with MN sensitised against rituximab.